2014
DOI: 10.1590/1677-3225v13n4a09
|View full text |Cite
|
Sign up to set email alerts
|

Pharyngeal airway space cephalometric evaluation in transverse maxillary deficient patients after SARME

Abstract: Aim:To evaluate prospectively the upper airway of 16 patients submitted to surgically assisted rapid maxillary expansion. Methods: Volumetric tomography acquisitions were done preoperatively (T1) and after six months postoperatively (T2), the slices were obtained from the hard palate to the third cervical vertebra (C3), the images were imported and reconstructed in the Dolphin software for 2D definition of the upper airway. A cephalometric radiograph was generated by the software, the cephalometric points were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In this context, it is observed that the movement of the facial skeleton produces changes in the tension of the soft tissues and muscles inserted in the jaw. Soft palate, tongue, hyoid bone and associated musculature are directly or indirectly inserted in the jaw, therefore movements in those structures induce alterations in the oral and nasal cavity and on the PAS [1][2][3][4][5] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, it is observed that the movement of the facial skeleton produces changes in the tension of the soft tissues and muscles inserted in the jaw. Soft palate, tongue, hyoid bone and associated musculature are directly or indirectly inserted in the jaw, therefore movements in those structures induce alterations in the oral and nasal cavity and on the PAS [1][2][3][4][5] .…”
Section: Introductionmentioning
confidence: 99%
“…Studies 1,4-5 have been conducted to quantify the regular measurements of PAS, as well as the measurements in patients diagnosed with obstructive sleep apnea (OSA). Those studies are based on lateral cephalometric analysis 1,6 and indicate that the most significant anatomic variation is the lower position of the hyoid bone and consequently the lower position of the tongue base in OSA patients [4][5]7 .…”
Section: Introductionmentioning
confidence: 99%